Nickel‐Catalyzed Decarbonylative Borylation of Amides: Evidence for Acyl C−N Bond Activation. (3rd June 2016) - Hu, Jiefeng; Zhao, Yue; Liu, Jingjing; Zhang, Yemin; Shi, Zhuangzhi
Abstract: A nickel/N‐heterocyclic carbene catalytic system has been established for decarbonylative borylation of amides with B2 nep2 by C−N bond activation. This transformation shows good functional‐group compatibility and can serve as a powerful synthetic tool for late‐stage borylation of amide groups in complex compounds. More importantly, as a key intermediate, the structure of an acyl nickel complex was first confirmed by X‐ray analysis. Furthermore, the decarbonylative process was also observed. These findings confirm the key mechanistic features of the acyl C−N bond activation process.